El impacto de la actividad universitaria sobre el medio ambiente - Ull Solís, A. (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2017)
Se hace un repaso a la situación actual respecto a la ambientalización o sostenibilización en todos los ámbitos de la universidad (la docencia, la investigación y la vida universitaria). Palabras claves: universidad; sostenibilidad; gestion. The environmental impact of university’s activity This article is a review of the present situation with respect to the sustainability attended all the scopes of the university becomes (teaching, the investigation and the university life). Keywords: university; sustainability; management.